Living with the Sea - community fish stock management for conservation and cohesion: a comparative study between Greece and Japan - Vlachopoulou, Eirini Ioanna; Βλαχοπούλου, Ειρήνη Ιωάννα (2019)
Η διδακτορική διατριβή δεν πραγματοποίηθηκε στα πλαίσια κάποιου μεταπτυχιακού προγράμματος